Development, characterisation and evaluation of novel approaches to improve the lifetime performance of amine-based materials for carbon capture in power plants - Sun, Yuan (2018)
Carbon capture and storage (CCS) is considered to be one of the strategically important carbon abatement technologies that can be used to effectively reduce the carbon emissions from fossil fuel power plants and other large scale industrial processes, which are the major stationary sources of greenhouse carbon emissions. Compared to other capture technologies, solid adsorbents looping technology (SALT) based post-combustion carbon capture, an alternative to the state-of-the-art energy intensive amine scrubbing process, is widely viewed as being the most viable technology that can be used as either as a retrofit to existing power plants or new build capacity. The potential success of SALT technology is largely determined by the development of novel CO2 adsorbents. Amine immobilized solid adsorbents are highlighted to be used in SALT technology due to their high CO2 selectivity (CO2/N2 >1000), suitable adsorption temperature and tolerance of moisture. Although they have so much advantages on carbon capture, the oxidation and degradation of solid amines are still a significant problem to be overcome. The degradation of the amine adsorbent can lead to a reduction in CO2 capture performance and selectivity, an increase in the process cost and corrosion problems. The aim of this project is to 1) develop new solid adsorbent materials with higher CO2 capture ability and superior adsorption-desorption lifetime performance; 2) to investigate effective measures to minimise or effectively prevent the thermal and oxidative degradation of the sorbent materials; 3) to explore approaches that can rejuvenate the degraded sorbents for re-use or convert them into other value-added products.